PENGARUH ARTIFICIAL AGING DAN NATURAL AGING TERHADAP KEKERASAN DAN STRUKTUR MIKRO PENGECORAN LOGAM PISTON Al-Si - Edriyanto, Edriyanto; Balaka, Ridway; Aminur, Aminur (Teknik Mesin Universitas Halu Oleo, 2017)
The purpose of this research is to know the effect of artificial aging and natural aging on increasing hardness and micro structure of Al-Si alloy recycling. The material used in this research is Al-Si alloy which comes from motorcycle piston scrap which is casted like piston (prototype). The casting method used is acasting wherein a liquid metal is poured into a mold without pressure. Piston scrap is melted with 700????C temperature, on induction furnace for 1 hour and poured into die casting. Product of castings of prototype motorbike piston are prepared to be specimen followed by artificial aging and natural aging process with holding time 1-3 hour to test micro structure and hardness test of vickers method.Vickers hardness test results show that the maximum hardness value of aritifiacial aging specimens is 132,16 Kg / mm² with 3 hours hold time, and the lowest hardness value is 110,31 Kg / mm² with 1 hour hold time. While for themaximum hardness value of natural aging samples is 101,57 Kg / mm² with 3 hour hold time, while the lowest hardness value is obtained equal to 82,53 Kg / mm². With result of observation of micro structure of each sample undergoes structure change.Keywords: Metal casting, natural aging, artificial aging, hardness, and micro struktur.